Dynamics of White Clover Decomposition in a Southeastern Bermudagrass Lawn. (1st September 2013) - McCurdy, James D.; McElroy, J. Scott; Guertal, Elizabeth A.; Wood, C. Wesley
Abstract : Clover ( Trifolium spp.) inclusion within maintained turfgrass is a proposed means of increasing turfgrass sustainability; yet, little is known of the N contribution and C sequestration from decaying clover foliage. An in situ decomposition study was conducted in Auburn, AL, to quantify C and N release from the decomposition of white clover ( T. repens L.) foliage within a bermudagrass lawn ( Cynodon dactylon (L.) Pers. × C. transvaalensis Burtt Davy). Fresh white clover was applied during March, June, and December and was retrieved periodically after application. Four parameter double exponential decay models were used to describe clover mass as well as N and C loss. These models reveal important features of white clover decomposition; mainly that white clover is composed of a quickly decaying labile fraction. White clover litter applied at 0.5 kg fresh weight (FW) m –2 potentially contributed between 2.9 to 4.2 g N m –2, with more than half available for mineralization between 10 and 73 d after application, depending on time of year. Given that clover populations are regenerative, litter deposited during mowing events may be considered a viable N source to sustain healthy turf. Knowledge of the decomposition of clover within turf swards will enable turfgrass researchers and professionals to more accurately predict nutrient contribution to associated grasses and help optimize supplemental fertilizer recommendations.